Contribution of linoleic acid to the formation of advanced glycation end products in model systems during heat treatment - Xin Zhao; Lu Yue; Xincheng Liu; Ling Liu (Czech Journal of Food Sciences, 2017)
Advanced glycation end products (AGEs) are glycosylated metabolic products generated in vivo and are associated with aging-related diseases. They are also formed during heat treatment in food processing. In this work, we investigated the contribution of linoleic acid (LA) to AGE formation using a protein/glucose model. An electronic tongue, denaturing polyacrylamide gel electrophoresis, electron spin resonance spectroscopy, circular dichroism, and ultraperformance liquid chromatography-tandem mass spectrometry were used to analyse reaction intermediates and reactive radical formation. The results show that LA is the key factor responsible for the change in flavour including the rapid triggering of glycation reactions. The amount of lipid-induced reactive radicals was significantly higher than in the non-fat system, radical generation in the non-fat system was gradually quenched after a robust radical-yielding reaction in the first 25 minutes. Subsequent unsaturated lipid oxidation, and AGE accumulation surpass Maillard reaction-only outcomes. Initial LA-induced changes in protein structure are followed by glycation and are enhanced by hydrophobic interactions and increased carbonyl levels resulting from lipid oxidation. These findings implicate lipids and lipid oxidation as the main factors responsible for AGE formation during the processing of fat-rich unsaturated fatty acid-containing foods.